Evaluating occupational performance coaching to support fatigue management for people with multiple sclerosis: A feasibility study. (September 2022) - Askari, Sorayya; Kessler, Dorothy; Smyth, Penelope; Finlayson, Marcia
Objective: To determine the feasibility of adding coaching sessions to a website (MS INFoRM) that supports self-directed fatigue management for people with multiple sclerosis (PwMS). Design: Double-blind, parallel-group feasibility study. Participants and setting: Twenty-six PwMS, who experienced severe fatigue (fatigue severity scale > 5.4), were recruited from participants who were ineligible for the main trial testing on the MS INFoRM website. Intervention: Six 45-to-60-min sessions of one-on-one coaching plus access to the MS INFoRm website compared to two check-in phone calls plus access to the MS INFoRm website. Both study arms took place over 3 months. Main measures: Feasibility parameters included proportion eligible of those screened; proportion consented; missing data; retention and adherence rates. Acceptability was explored through qualitative interviews. Secondary outcomes (self-efficacy and fatigue impact) were measured at baseline and post-intervention. Results: 76 people were invited to participate in this add-on study. 40 were interested and screened: 32 were eligible, 26 consented, and were randomized (mean age: 48.5 yrs (SD: 8.7), mean disease duration: 11.5 yrs). Retention was 85% (22 out of 26). Coaching adherence was high (86% attended ⩾ 5 sessions). At 3 months, people in the intervention group showed more improvements in self-efficacy and fatigue impact compared to the comparison group, however, the difference was not statistically significant ( p  = 0.471 and p  = 0.147, respectively). The intervention was well-received by the participants and there were no adverse events. Conclusion: Combining one-on-one coaching sessions along with web-based interventions is feasible and appreciated by the participants, and worth exploring further in a larger trial.